2017
DOI: 10.1021/acs.jpcc.7b03126
|View full text |Cite
|
Sign up to set email alerts
|

Inducing Porosity on Hollow Nanoparticles by Hypervelocity Impacts

Abstract: The large surface-to-volume ratio of hollow palladium nanoparticles (hNPs) offers room to improve their hydrogen storage capacity as well as their catalytic activity. However, a less explored possibility is to use, in addition, the internal cavity. Here we explore, through classical molecular dynamics, the possibility of boring channels across the hNP wall by collision with solid Pd nanoprojectiles at high velocities, as well as their resilience to maintain their spherical geometry. We choose a stable hNP with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 51 publications
0
9
0
1
Order By: Relevance
“…However, Shan et al proved that CdSe hNPs of about 500 nm can be subject to large stress without collapsing. Moreover, it was recently shown that hNPs of sizes no larger than 20 nm can withstand even hypervelocity impacts . In addition, several authors have suggested that hollow interior macroscopic spherical particles could be used as protective coating for space vehicles. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Shan et al proved that CdSe hNPs of about 500 nm can be subject to large stress without collapsing. Moreover, it was recently shown that hNPs of sizes no larger than 20 nm can withstand even hypervelocity impacts . In addition, several authors have suggested that hollow interior macroscopic spherical particles could be used as protective coating for space vehicles. …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was recently shown that hNPs of sizes no larger than 20 nm can withstand even hypervelocity impacts. 12 In addition, several authors have suggested that hollow interior macroscopic spherical particles could be used as protective coating for space vehicles. 13−15 Highly porous materials, such as aerogels, 16 nanofoams, 17,18 and bioinspired composites, 19 are also very attractive, since they display a combination of flexibility and toughness.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Each hNP, with a desired radius and thickness ( t ), was made by carving up a polycrystalline Au sample, with a specific average grain size ( d ), which is controlled through a Voronoi tessellation algorithm. , To avoid high energy grain boundaries or atom overlapping, we removed from the sample all the atoms with energies higher than 50 eV, principally from the grain boundary interface; then, we relaxed the polycrystal by using a conjugate gradient method coupled with a box relaxation algorithm. Also, to allow grain boundary re-accommodation, and to circumvent spurious effects due to high energy grain boundaries, we annealed the sample at a temperature of T = 2 T m /3, where T m is the Au melting point.…”
Section: Methodsmentioning
confidence: 99%
“…Currently there is more of an emphasis on Pd hydride systems as it pertains to potential advances in the hydrogen economy [2]. In recent years, a wide variety of shapes [3][4][5] and sizes [6,7] have been studied for improved Pd hydride systems. As these complicated Pd nanostructures see more interest in the academic setting, industrial implications where quality and control of the size and structure of a potential product must be realized.…”
Section: Introductionmentioning
confidence: 99%